What Matters Most to Patients and Rheumatologists? A Discrete Choice Experiment in Rheumatoid Arthritis - Díaz-Torné, Cesar (Adv Ther, 2020)
INTRODUCTION: To determine patient and rheumatologist preferences for rheumatoid arthritis (RA) treatment attributes in Spain and to evaluate their attitude towards shared decision-making (SDM). METHODS: Observational, descriptive, exploratory and cross-sectional study based on a discrete choice experiment (DCE). To identify the attributes and their levels, a literature review and two focus groups (patients [P] = 5; rheumatologists [R] = 4) were undertaken. Seven attributes with 2–4 levels were presented in eight scenarios. Attribute utility and relative importance (RI) were assessed using a conditional logit model. Patient preferences for SDM were assessed using an ad hoc questionnaire. RESULTS: Ninety rheumatologists [52.2% women; mean years of experience 18.1 (SD: 9.0); seeing an average of 24.4 RA patients/week (SD: 15.3)] and 137 RA patients [mean age: 47.5 years (SD: 10.7); 84.0% women; mean time since diagnosis of RA: 14.2 years (SD: 11.8) and time in treatment: 13.2 years (SD: 11.2), mean HAQ score 1.2 (SD: 0.7)] participated in the study. In terms of RI, rheumatologists and RA patients viewed: time with optimal QoL: R: 23.41%/P: 35.05%; substantial symptom improvement: R: 13.15%/P: 3.62%; time to onset of treatment action: R: 16.24%/P: 13.56%; severe adverse events: R: 10.89%/P: 11.20%; mild adverse events: R: 4.16%/P: 0.91%; mode of administration: R: 25.23%/P: 25.00%; and added cost: R: 6.93%/P: 10.66%. Nearly 73% of RA patients were involved in treatment decision-making to a greater or lesser extent; however, 27.4% did not participate at all. CONCLUSION: Both for rheumatologists and patients, the top three decision-making drivers are time with optimal quality, treatment mode of administration and time to onset of action, although in different ranking order. Patients were willing to be more involved in the treatment decision-making process. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12325-020-01258-5) contains supplementary material, which is available to authorized users.